2021
DOI: 10.3892/etm.2021.10912
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of miRNA‑23a in diabetic retinopathy

Abstract: The present study aimed to investigate the expression of microRNA (miRNA)-23a in blood and tear samples from diabetic retinopathy (DR) patients. Blood and tear samples were obtained from 33 patients with proliferative DR. Additionally, a rat model of DR was established. Reverse transcription-quantitative PCR was used to determine vascular endothelial growth factor (VEGF) mRNA and miRNA-23a expression levels, while ELISA and western blot analysis were performed to determine protein expression levels. Bioinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Circular RNA COL1A2 contributes to HG-induced proliferation, migration, and vascular permeability in HRMECs and retinal angiogenesis in mice with diabetes by competing with VEGF mRNA for binding to miR-29b ( 30 ). There are many other miRNAs, such as miR-15b, miR-23a, miR-205-5p, and miR-150-5p, which directly interact with VEGF in retinal endothelial cells and are involved in angiogenesis in DR ( 31 - 34 ). This study identified miR-101-3p as a direct regulator of VEGFA in HRMECs.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA COL1A2 contributes to HG-induced proliferation, migration, and vascular permeability in HRMECs and retinal angiogenesis in mice with diabetes by competing with VEGF mRNA for binding to miR-29b ( 30 ). There are many other miRNAs, such as miR-15b, miR-23a, miR-205-5p, and miR-150-5p, which directly interact with VEGF in retinal endothelial cells and are involved in angiogenesis in DR ( 31 - 34 ). This study identified miR-101-3p as a direct regulator of VEGFA in HRMECs.…”
Section: Discussionmentioning
confidence: 99%
“…Tear miRNA composition has been shown to be altered in DR patients. Sun et al found that miR-23a expression was decreased in the tears and serum of patients with type 2 diabetes or pre-diabetes compared to controls [ 18 ]. This is intriguing as miR-23a has been linked to a potential inhibitory role on VEGF, an important factor in the development of DR and blood vessel growth [ 114 , 115 ].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Advances in miRNA quantitation, paired with the simple, non-invasive collection methods of tears [ 13 ], entice mass participant collection [ 14 ] and physician engagement [ 15 ], which is essential for biomarker validation. Moreover, the importance of studying the relationship between tear composition and ocular health has become more apparent in recent years, and a multitude of studies have reported variations in tear miRNA content across different pathologies [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The cohesive relationship between miRNAs, the tear film, and health makes tear miRNAs pertinent options as noninvasive and low-cost diagnostic markers for numerous pathologies [ 13 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, plasma miR-26a-5p levels and retinal nerve fiber layer thickness are positively correlated; this may be a potential biomarker for early-stage DR [ 55 ]. Sun et al found that miRNA-23a levels are significantly decreased in the blood and tears of patients with DR. Overexpression of miRNA-23a significantly inhibits retinal microvascular EC proliferation by reducing VEGF expression [ 56 ]. miR-1281 was found to be considerably overexpressed in serum samples from patients with DR and could, therefore, be a new target in treating DR [ 57 ].…”
Section: Mirnasmentioning
confidence: 99%